Influence of the size of the paddles in front crawl stroke - Monteil, K. M.; Rouard, A. H. (Biomechanics and Medicine in Swimming. Swimming Science VI, 1992)
Many coaches use paddles in the training programme of their swimmers. The purpose of the research was to study the influence of the size of these paddles on biomechanical parameters (total time of the stroke, hip displacement per stroke, phases of the stroke) in front crawl swimming. Seven long (n = 4) and short (n = 3) distance swimmers were examined. Each subject performed 25 m swims with and without three different paddles. Electrical activity of five muscles of the upper limb were recorded with a multichannel telemetric system. Underwater sideviews were captured simultaneously. Results showed that the use and size of the paddles did not change the temporal partitioning of the phases and the hip distance covered per stroke. Electromyographic results indicated similar recruitment patterns through the different tests. The M. biceps brachii had the lowest firing, but the use of paddles increased its activity during the pull phase. There was no linear increase in muscle activity with the increase of size of the paddles. The short distance swimmers seemed to be the more disturbed by the use and size of the paddles.